Reliability generalization meta-analysis of the food neophobia scale: Turkish sample - Eray Polat; Serkan Çalışkan (Journal of Tourism, Heritage & Services Marketing)
Purpose: The Food Neophobia Scale developed by Pliner and Hobden (1992) has been widely utilized globally and in Turkey for many years to measure people's fear of new foods. This study aims to determine the mean value by conducting a reliability generalization meta-analysis for the reported reliability coefficients of individual studies in Turkey's tourism field, which employed Pliner and Hobden's scale to investigate food neophobia. Additionally, this study explores variations in the mean value among subgroups.